2017
DOI: 10.1021/acs.biochem.7b00378
|View full text |Cite
|
Sign up to set email alerts
|

Caulobacter crescentus Cell Cycle-Regulated DNA Methyltransferase Uses a Novel Mechanism for Substrate Recognition

Abstract: Caulobacter crescentus relies on DNA methylation by the cell cycle-regulated methyltransferase (CcrM) in addition to key transcription factors to control the cell cycle and direct cellular differentiation. CcrM is shown here to efficiently methylate its cognate recognition site 5'-GANTC-3' in single-stranded and hemimethylated double-stranded DNA. We report the K, k, k, and K for single-stranded and hemimethylated substrates, revealing discrimination of 10-fold for noncognate sequences. The enzyme also shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…Lon exhibited an ∼14-fold higher affinity to DNA than to CcrM. Recent studies of DNA recognition by CcrM reported an equilibrium dissociation constant of 108 ± 20 nM for double-stranded DNA (22). A quantitative Western blot was performed to determine the in vivo concentration of CcrM and Lon at 120 min into the swarmer cell cycle, using purified CcrM and Lon to calibrate a standard curve.…”
Section: Ccrm Protein Turnover Undergoes Distinct Dynamics In Swarmermentioning
confidence: 99%
“…Lon exhibited an ∼14-fold higher affinity to DNA than to CcrM. Recent studies of DNA recognition by CcrM reported an equilibrium dissociation constant of 108 ± 20 nM for double-stranded DNA (22). A quantitative Western blot was performed to determine the in vivo concentration of CcrM and Lon at 120 min into the swarmer cell cycle, using purified CcrM and Lon to calibrate a standard curve.…”
Section: Ccrm Protein Turnover Undergoes Distinct Dynamics In Swarmermentioning
confidence: 99%
“…DNA Binding by CcrM is a prerequisite for its chromosome methylation activity. Given that DNA-bound Lon protease is active throughout the cell cycle, we hypothesized that CcrM, which has been shown to processively move on DNA (Berdis et al, 1998; Woodcock et al, 2017), could be recognized by Lon bound to DNA. To test this hypothesis, we attempted to reconstitute this interaction in vitro using three different DNA probes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a ~14-fold-weaker affinity between LonS674A * and CcrM than between LonS674A * and DNA Probe 1. Recent studies on DNA recognition by CcrM reported an equilibrium dissociation constant of 108 ± 20 nM for double-stranded DNA (Woodcock et al, 2017). We performed a quantitative Western blot to determine the concentration of CcrM in vivo at the 120 minutes-post-synchrony timepoint, using purified CcrM to calibrate a standard curve (Figure S3D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique revealed that most GANTC motifs are efficiently methylated by CcrM on the C. crescentus genome, highlighting the efficiency of this enzyme (Kozdon et al ., ; Gonzalez et al ., ). It is unclear whether CcrM is a processive enzyme that remains attached to DNA and methylates multiple GANTC motifs before dissociating from the DNA (Berdis et al ., ; Shier et al ., ; Woodcock et al ., ) or a distributive enzyme that dissociates after each methylation reaction (Albu et al ., ; Maier et al ., ).…”
Section: Introductionmentioning
confidence: 99%